2012
DOI: 10.1210/jc.2011-1923
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ovarian Reserve Based on Hormonal Parameters, Ovarian Volume, and Antral Follicle Count in Women with Type 2 Diabetes Mellitus

Abstract: Objective: The aim of this study was to evaluate ovarian reserve of women with type 2 diabetes mellitus (T2DM). Methodology:Eighty-nine women with T2DM and 73 healthy controls were enrolled and divided into three age groups [group 1 (20 -29 yr), seven diabetics and 18 healthy controls; group 2 (30 -39 yr): 35 diabetics and 35 healthy controls; and group 3 (40 -49 yr): 47 diabetics and 20 healthy controls]. All participants were subjected to transvaginal ultrasonographic examination on the third day of their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 48 publications
2
29
1
Order By: Relevance
“…However, insulin resistance could also decrease granulosa cell function, which could lead to reduced ovarian function and therefore lower AMH levels (17,18). Our hypothesis fits with the result of a study in type 2 diabetes mellitus (T2DM) patients, in which AMH levels were significantly lower than in healthy controls (36), which was possibly a result of insulin resistance in the T2DM patients. Furthermore, the fact that stringent glycemic control in diabetic patients improves menstrual cycles and fertility rates underlines the hypothesis that prolonged hyperglycemia and chronic complications of diabetes negatively affect ovarian reserve (37).…”
Section: Discussionsupporting
confidence: 86%
“…However, insulin resistance could also decrease granulosa cell function, which could lead to reduced ovarian function and therefore lower AMH levels (17,18). Our hypothesis fits with the result of a study in type 2 diabetes mellitus (T2DM) patients, in which AMH levels were significantly lower than in healthy controls (36), which was possibly a result of insulin resistance in the T2DM patients. Furthermore, the fact that stringent glycemic control in diabetic patients improves menstrual cycles and fertility rates underlines the hypothesis that prolonged hyperglycemia and chronic complications of diabetes negatively affect ovarian reserve (37).…”
Section: Discussionsupporting
confidence: 86%
“…The present findings, showing a significant reduction in ovarian volume in patients with MetS, are in agreement with results showing delayed menarche and irregular menstruation in patients with type 1 diabetes [17] and significant reductions in ovarian volume and AFC in patients with type 2 diabetes aged 20–29 years [1], compared with age-matched controls. In contrast, ovarian volumes in subjects aged 20–39 and 40– 49 years were similar in those with MetS and healthy controls.…”
Section: Discussionsupporting
confidence: 93%
“…Female fertility, by spontaneous conception or assisted reproductive techniques, decreases significantly with age, a reduction that may be due to the reduction in the number of primordial follicles over time [1-3]. Ovarian reserve is a measure of the reproductive potential of a woman in relation to primordial follicle count and oocyte quality.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these findings, Verit et al [54] demonstrated that diminished ovarian reserve (determined by antral follicle count (AFC) and estrogen level) was associated with increased LDL-c level, triglyceride, and CRP levels, in addition to decreased insulin sensitivity and decreased HDL-c levels. This statement is further supported by the finding of lower AFC in women with type 2 diabetes compared to healthy controls over several age groups in a cross-sectional study [55]. Ovarian volume measured by ultrasound was similarly reduced in women with metabolic syndrome compared to healthy controls, although similar FSH levels between the groups raise doubt on the implications for true differences in ovarian reserve status [56].…”
Section: Discussionmentioning
confidence: 85%